Vitamin D for the prevention of diseases in children: A rebuttal to the 2024 Endocrine Society Clinical Practice Guideline - Nwosu, Benjamin Udoka (Frontiers in Endocrinology, 2025)
The recent 2024 Endocrine Society Clinical Practice Guideline on Vitamin D for the prevention of diseases has become a source of controversy among medical professionals and the lay public. This Review rebuts the recommendations from this Guideline for infants, children, adolescents, pregnant women, and dark-skinned individuals. It rejects the one-size-fits-all recommendations and provides the data for precision-medicine-guided vitamin D screening and supplementation in these populations.